2020
DOI: 10.1177/2325967120917674
|View full text |Cite
|
Sign up to set email alerts
|

Healing Status of Meniscal Ramp Lesion Affects Anterior Knee Stability After ACL Reconstruction

Abstract: Background: Although the biomechanical importance of the ramp lesion in the anterior cruciate ligament (ACL)–deficient knee has been demonstrated, there is no clear consensus on the appropriate treatment for ramp lesions during ACL reconstruction. Purpose: To compare the postoperative outcomes for ramp lesions between patients treated with all-inside repair through the posteromedial portal and those whose ramp lesions were left in situ without repair during ACL reconstruction. We also determined whether ramp l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 26 publications
3
59
1
Order By: Relevance
“…29 It is our opinion that if a posteromedial portal is being created for abrasion and trephination, then it is logical to also repair the ramp lesion. This view is supported by the recent study by Hatayama et al, 30 who compared the postoperative outcomes for ramp lesions between patients treated with all-inside repair through the posteromedial portal and those whose ramp lesions were left in situ without repair during ACL reconstruction. The authors found that healing rates of ramp lesions were significantly better in the repaired group than in the non-repaired group.…”
Section: See Related Article On Page 2921mentioning
confidence: 77%
See 1 more Smart Citation
“…29 It is our opinion that if a posteromedial portal is being created for abrasion and trephination, then it is logical to also repair the ramp lesion. This view is supported by the recent study by Hatayama et al, 30 who compared the postoperative outcomes for ramp lesions between patients treated with all-inside repair through the posteromedial portal and those whose ramp lesions were left in situ without repair during ACL reconstruction. The authors found that healing rates of ramp lesions were significantly better in the repaired group than in the non-repaired group.…”
Section: See Related Article On Page 2921mentioning
confidence: 77%
“…They also found that anterior laxity was significantly greater in the knees with unhealed ramp lesions compared with the knees in which the ramp lesions had healed. 30 DePhillipo et al 24 have shown that patients with combined ACL tear and ramp lesions have increased preoperative knee anteroposterior and rotational knee laxity, as demonstrated by grade 3 Lachman (44% vs 6%) and pivotshift (38% vs 12%) tests when compared with ACL tear group without ramp lesion (P .005 for both). Thus, it makes more sense to repair the ramp lesion to restore the physiological knee stability and kinematics.…”
Section: See Related Article On Page 2921mentioning
confidence: 96%
“… 5 Unrepaired ramp lesions can cause failure of ACL reconstruction, and acute rupture or chronic deficiency of the ACL can also cause ramp lesions owing to anteroposterior and rotational laxity. 5 , 9 , 10 , 11 , 12 Thus, unstable ramp lesions need to be repaired to ensure successful ACL repair. 5 , 13 However, unlike other meniscal injuries, ramp lesions can easily be misdiagnosed or overlooked.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Various treatments of MRL exist, but the most definite and frequently applied is lesion repair. 19 …”
Section: Overview Of Ramp Lesion Of the Medial Meniscusmentioning
confidence: 99%
“…To conclude it all, patients who underwent MRL repair show significantly higher subjective scores, healing rates and significantly lower anterior laxity than those who did not. 19 Thus, surgical treatment should be advocated in all unstable lesions. 43 …”
Section: Arthroscopy and Repairmentioning
confidence: 99%